SANDSTONE QUALITY ASSESSMENT FROM CORE DATA OF SANTUL FORMATION, TARAKAN BASIN BASED ON PETROGRAPHY AND ROUTINE CORE ANALYSIS - Yuniardi, Yuyun; Muljana, Budi; Mardiana, Undang; Hardiyono, Adi; Nur, Andi Agus; Mohammad, Febriwan; Alfadli, Muhammad Kurniawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
This study analysss the quality of sand stone as reservoir in Sentul Formation, Tarakan Basin, based on petrography and routine core analysis. The quality of the sandstone in facies A (depth of 1743.75–1747.28m) is moderate. This assessment is based on the porosity value of routine core analysis from 19.48% to 27.88%, and permeability value from 25mD to 213 mD. The sandstone quality of facies B (depth of 1741.80 m–1743.75m) is good, this is based on the value of the porosity from routine core ranges from 23.34% to 26.71% and 83-359 mD of permeability value. The quality of sandstone in facies C (depth of 1737.65m–1737.75m) is good. The differences of the quality affected by the various level of compaction, sorting, and contact between the grains. The presence of carbon material and laminated clay also led to differences in the quality of the reservoir through inter-granule space filling. Sandstone mineral composition of each facies dominated by mono crystalline quartz which is chemically relatively stable, so that the cementation and replacement processes do not overly affect the porosity and permeability.